Three novel homozygous point mutations and a new polymorphism in the COL17A1 gene: relation to biological and clinical phenotypes of junctional epidermolysis bullosa. - Schumann, H (1997)
Junctional epidermolysis bullosa (JEB) is a clinically and biologically heterogeneous genodermatosis, characterized by trauma-induced blistering and healing without scarring but sometimes with skin atrophy. We investigated three unrelated patients with different JEB phenotypes. Patients 1 and 2 had generalized atrophic benign epidermolysis bullosa (GABEB), with features including skin atrophy and alopecia. Patient 3 had the localisata variant of JEB, with predominantly acral blistering and normal hair. All patients carried novel homozygous point mutations (Q1016X, R1226X, and R1303Q) in the COL17A1 gene encoding collagen XVII, a hemidesmosomal transmembrane component; and, therefore, not only GABEB but also the localisata JEB can be a collagen XVII disorder. The nonsense mutations led to drastically reduced collagen XVII mRNA and protein levels. In contrast, the missense mutation allowed expression of abnormal collagen XVII, and epidermal extracts from that patient contained polypeptides of normal size, as well as larger aggregates. The homozygous nonsense mutations in the COL17A1 gene were consistent with the absence of the collagen from the skin and with the GABEB phenotype, whereas homozygosity for the missense mutation resulted in expression of aberrant collagen XVII and, clinically, in localisata JEB.